Using Instability of a Non-stoichiometric Mixed Oxide Oxygen Evolution Catalyst As a Tool to Improve Its Electrocatalytic Performance - Kasian, Olga; Geiger, Simon; Schalenbach, Maximilian; Mingers, Andrea M.; Savan, Alan; Ludwig, Alfred; Cherevko, Serhiy; Mayrhofer, Karl (Electrocatalysis, 2018)
Owing to their superior electrocatalytic performance, non-stoichiometric mixed oxides are often considered as promising electrocatalysts for the acidic oxygen evolution reaction (OER). Their activity and stability can be superior to those of the state-of-the-art IrO2 catalysts, although the exact nature of this phenomenon is not yet understood. In the current work, a Ir0.7Sn0.3O2-x thin-film electrode is taken as a representative example for a thorough evaluation of OER activity of the non-stoichiometric oxides. Complementary activity and stability analysis of Ir0.7Sn0.3O2-x electrodes is achieved using a setup based on an electrochemical scanning flow cell and ICP-MS. The obtained ICP-MS data presents an unambiguous proof of the preferential dissolution of the less noble Sn from the mixed oxide during OER. While less than a monolayer of Ir is dissolved after a prolonged electrolysis of 1400 min during which its dissolution rate drops to near zero, the amount of Sn lost is ten monolayers. The latter finding is confirmed by XPS analysis, which besides showing Ir surface enrichment also indicates a gradual transformation of Ir-0 to Ir-III species. This transition is beneficial for electrode activity, as the overpotential for OER at j = 5 mA cm(-2) was decreasing up to 300 mV. The increase in electrode activity is attributed to several mechanisms including generation of Ir-III active sites and overall surface area increase. A generalized description of OER catalysis by Ir-based materials is given, including data from the current work as well as from other Ir-based mixed oxides, such as Ir-Ru-O and Ir-Ni-O.
Keywords: Oxygen evolution reaction; Water splitting; Electrocatalysis; Iridiumtinoxide; Non-stoichiometric mixed oxide; Dissolution